Private Space as a site for Anti-Colonial Imagination: Critical Study of Twilight in Delhi - Alam, Khurshid (Journal of Research in Humanities, 2023)
In my paper, I intend to conduct a discourse analysis of Ahmed Ali’s Twilight in Delhi to demonstrate how living by narratives has a therapeutic effect on our injured sense of national pride. In Ahmed Ali, the protagonist, Mir Nihal feels frustrated at the political and cultural disempowerment in the public sphere. But he is incapacitated to put an active resistance to the colonizer. Thus he develops an aesthetic or in Chatterji’s words spiritual mode of resistance in the private realm of imagination. Whenever he feels insulted at the hands of the colonizer, he takes refuge in an imagined past when the Muslim rulers enjoyed absolute political power. He views the Muslim past in India as a linearly constructed discourse in which the Muslims and Hindus enjoyed an exemplary social and cultural harmony. My argument is that it is an attempt to narrativize the past and to create a benign, monolithic Muslim identity. Mir Nihal does not say a single word about the Muslim colonization of India. In my view, it is related to the politics of building historical narratives. Since Mir Nihal wants to regain lost power, his narrative remains silent on the Hindu perspective as it may become fatal for an imagined national unity needed to fight back the colonizer. His idea of nationhood draws strength from the selective narration of the past, the mythological past of India during the reign of Asoka and Chundergupt a Maurya and the arrival of the Muslim.